A Tripled Fixed Point Theorem in C∗-Algebra-Valued Metric Spaces and Application in Integral Equations. (13th April 2021) - Parvaneh, Vahid; Bonab, Samira Hadi; Hosseinzadeh, Hasan; Aydi, Hassen
Abstract : Our aim is to establish a tripled fixed and coincidence point result on generalized C ∗ -algebra-valued metric spaces. We present an example on matrices. At the end, we give an application on integral equations.